Analysis of heavy metals in the human hair to establish the e-waste toxicity among the Filipino informal recyclers located at various e-waste dumpsites in and around Manila, Philippines - Alam, Zeba F. (Animo Repository, 2018)
The landfill areas of Tondo and Payatas located at the outskirts of Metro Manila are used for the dumping and dismantling of e-waste in the Philippines. The dismantling of e-waste by informal recyclers causes the leaching out of harmful substances such as heavy metals thereby contaminating the environment and the human population living in close proximity to e-waste landfills. This study was done to assess the contamination status by measuring the heavy metals in the hair of informal recyclers compared to heavy metal levels in the control group. Hair samples were collected and analysed using atomic absorption spectroscopy. Ten heavy metals were considered including essential minerals, Zn, Mg, K, Fe, Mn as well as Cd, Cu, Cr, Pb and Ni (toxic metals related to e-waste). The preliminary investigations establish the presence of heavy metals in the hair samples of e-waste recyclers, which confirms the absorption of heavy metals from e-waste into the body. The concentrations of metals (copper, lead and potassium) were significantly higher in the hair samples of the informal recyclers than the control group. Pb was significantly higher than the permissible limits in recyclers from the Payatas dumpsite and Cu, Ni and Cd were significantly higher than the permissible limits in recyclers from the Tondo dumpsite. The results prove that human scalp hair can be used as biomarker to assess the extent of heavy metal exposure to informal recyclers engaged in e-waste recycling activities. © 2018 Technoscience Publications. All rights reserved.